Cartera de crédito vencida en la comercializadora “Doña Blanquita RDM” ubicada en el Cantón Puebloviejo en el periodo 2021 – 2022 - Herrera Soriano, Gloria Jhovanka (2023)
The present case study with the theme "Overdue credit portfolio in the Distributor "Doña Blanquita RDM" located in the Puebloviejo canton in the period 2021 - 2022", aims to analyze the overdue credit portfolio through the financial information of the company in order to identify the liquidity index that it has, and highlight the importance of proper management of accounts receivable and portfolio recovery so that the amounts owed by customers do not continue to increase. During the development of the investigation, theoretical bases related to accounts receivable, credit, past-due credit portfolio, financial indicators, and horizontal analysis were reviewed, such information was necessary and helpful for the preparation of the results. A qualitative and quantitative (mixed) approach was used, in addition the inductive-deductive method was used, and the interview was applied as a research instrument, which allowed us to identify how the company has been affected due to the increase in past-due portfolio. Among the results obtained, it was possible to show that the entity does not have adequate control of its credit portfolio, does not follow up on compliance with customer payments, which results in an increase in the level of delinquency.